Weevil resistance mechanisms in corn kernels - Santos, Jamilton P.; Foste, John E. (Pesquisa Agropecuaria Brasileira, 2014)
The built in maize weevil resistance in corn kernels is important because it gives protection to the threshed and unthreshed stored corn. Through a study conducted in this area it was possible to identify some resistant (R-Corn) and susceptible (S-Corn) com genotypes. Using these types of corn, two experiments were conducted to look for evidence of the resistance mechanisms involved in the maize weevil/corn grain relationship. Based on the results obtained from these experiments the following observations could be made: a) when the R-Corn and the S-Corn were offered simultaneously, the S-Corn attracted 14 times more weevils than the R-Corn; b) when only the R-Corn was offered, in seven days, a high weevil mortality occurred; c) the reproductive potential decreased in the weevils reared in the R-Corn in relation to those reared in the S-Corn; d) the source of food during the adult stage contributed more for the reproductive potential than during the developmental period; e) finally, one can conclude that the resistance in corn grain to maize weevil results from a joint effect of "antibiosis" and "antixenosis".